(untitled) (Sebha University Conference Proceedings, 2025)
Brainstorming is one of the most prominent educational strategies that contribute to the production of new ideas because it relies on open discussions to stimulate imagination, flexibility, and training in creative thinking. Its lack of use and reliance on the method of listening and memorizing academic vocabulary led to students’ lack of connection with their educational environment, as it focused on cognitive aspects only. Hence the research problem appears, represented in the following main question: “What is the effect of brainstorming in the Holy Qur’an and the Sunnah on the educational process?” The study aims to explain the importance and stages of brainstorming in the educational process, as well as revealing the impact of brainstorming applications in the Qur’an and Sunnah on the process. Educational: The researcher follows the inductive and analytical approach to extract the most important applications of brainstorming in the Qur’an and Sunnah and their impact on the educational process The researcher reached the most important results: The brainstorming strategy is one of the most successful educational methods used to present ideas freely and safely, away from confiscation, evaluation, or criticism .Brainstorming has an impact in stimulating enthusiasm for learning, helps develop students’ communication skills, and contributes to developing